Hubungan Kekerabatan Bahasa Bali dan Bahasa Ogan - Aditiawan, Zulvi; Suryati, Ni Made; Sutama, Putu (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2026)
Regional languages are languages spoken by ethnic groups in different regions. This study aims at examining the kinship relationship and determine the estimated time of separation between the Balinese and Ogan languages using a comparative historical linguistic approach. The data sources for this research are divided into two categories. The first is obtained from direct interviews with native speakers of Balinese and Ogan languages, ensuring authentic and contextual primary data. The second comes from secondary literature, such as Balinese dictionaries (e.g., standard dictionaries published by Balinese language institutions) and Ogan dictionaries, which provide verified lexical references. Data collection was conducted using the simak (observation) and cakap (interview) methods, in line with standard practices in field linguistics. The simak method employs basic techniques like sadap (covert audio recording) and advanced techniques such as libat cakap (involved conversation), bebas libat cakap (free conversation), rekam (audio recording), and catat (manual note-taking). Meanwhile, the cakap method uses basic pancingan techniques via written or spontaneous questions, followed by advanced techniques including cakap semuka (face-to-face), tan semuka (non-face-to-face, such as by phone), rekam, and catat. This approach ensures comprehensive data coverage in both oral and written forms. Data analysis adopts a combined design method known as concurrent triangulation. This process is supported by the intralingual comparison (padan intralingual) method, using basic techniques of hubung banding intralingual (intra-language element comparison). Advanced techniques include hubung banding menyamakan (identifying phonemic or semantic similarities) and hubung banding membedakan (highlighting structural differences). This approach enables accurate cognate calculation within the lexicostatistical framework. The data analysed includes 200 basic vocabulary words from the Swadesh list, processed using lexicostatistical and glottochronological techniques based on Keraf's (1983) theoretical framework. Through lexicostatistical techniques, the percentage of cognate words was calculated by identifying identical words, words showing phonemic correspondence, and words with similar phonetic environments. The analysis yielded 47 pairs of identical words, 29 pairs of words with phonemic correspondence, and 25 pairs of words with similar phonetic environments, for a total of 101 cognate word pairs, or approximately 50,5% of the total vocabulary compared. This figure indicates that Balinese and Ogan languages have linguistic connections even though they are classified as different languages. Glottochronology was then used to estimate the time of separation between the two languages based on the percentage of cognate words. The results of the calculation show that Balinese and Ogan began to diverge between 1,398 and 1,574 years ago, or around  to 451 – 627 CE if calculated from the year of the study, 2025. This finding indicates that both languages originated from the same proto-language within the Austronesian family but have undergone distinct developments over more than a thousand years